Hepatokines, bile acids and ketone bodies are novel Hormones regulating energy homeostasis - Garruti, Gabriella; Baj, Jacek; Cignarelli, Angelo; Perrini, Sebastio; Giorgino, Francesco (Frontiers in Endocrinology, 2023)
Current views show that impaired balance partly explains the fat accumulation leading to Obesity. Foetal malnutrition, early exposure to endocrine disrupting compounds also contribute to Obesity and impaired insulin secretion and/or sensitivity. Liver is playing a major role in systemic glucose homeostasis through hepatokines secreted by hepatocytes. Hepatokines influence metabolism through autocrine, paracrine and endocrine signalling and mediate the cross-talk between liver, non-hepatic target tissues and brain. Liver is also synthetizing bile acids (BAs) from cholesterol and secreting them into bile. After food consumption, BAs mediate digestion and absorption of fat-soluble vitamins and lipids in the duodenum. In recent studies BAs act not simply as fat emulsifier, but represent endocrine molecules regulating key metabolic pathways. Liver is also the main site of production of ketone bodies (KBs). In prolonged fasting, brain utilizes KBs as an alternative to CHO. In the last years, ketogenic diet (KD) became a promising dietary intervention. Studies in subjects undergoing KD show that KBs are important mediators of Inflammation and oxidative stress. The present review will focus on the role played by hepatokines, BAs and KBs in Obesity, and Diabetes prevention and management. It will also analyze positive effects of BAs, KD and hepatokine receptor analogues which might justify their use as new therapeutic approaches for metabolic and aging-related diseases.